A Comprehensive Cross-sectional Analysis of Prevalence of Congenital Color Vision Deficiency among Patients - Ahmed, Samra; Chaudhary, M. Mumtaz; Malik, Qurat ul Ain; Anwar, Adila; Saad, Hannia Talha (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: To determine the frequency of color vision impairment among Pakistani adults at Polyclinic Hospital Islamabad. Methodology: This descriptive, cross-sectional study was conducted at Federal Government Polyclinic Hospital, Islamabad. The research was conducted from March to May 2022, employing a consecutive non-probability sampling methodology. The study centred on a cohort of participants aged 10 to 55 who received medical attention at the Ophthalmology Outpatient Department. Sampling was done using the non-probability consecutive sampling technique. The sample size was 104 patients. All adults aged between 10-55 years were included except Patients having a history of Ocular or Neurological surgery, Trauma and Patients diagnosed with Diabetes or Hypertension were excluded. The gathered data was entered and analyzed using IBM SPSS Statistics version 20. Results: A total of 104 candidates underwent color vision assessment. 3.8% (4/104) of the candidates were color vision deficient. All of them were unaware of their condition. Conclusion: The screened Population showed color blindness in 3.8% of the candidates. All of the individuals were unaware of the condition.